Acute on chronic subdural hematoma in a female boxer: A case Rase report - Miele, V. J.; Carson, L.; Carr, A.; Bailes, J. E. (Medicine & Science in Sports & Exercise, 2004)
Introduction: Although the sport of female boxing has a long history, the activity's current popularity is unprecedented. As more women participate, we can expect them to experience many of the serious neurologic injuries observed in their male counterparts. We present the first reported subdural hematoma in a female secondary to boxing and critique management decisions made by the athlete's trainer/coach.